The impact of vocational college students' professional identity on academic achievement: Self-efficacy as a mediator - Lin, Yincai; Li, Xianyin (International Journal of Innovative Research and Scientific Studies, 2024)
To understand the current situation of the academic achievement of Chinese vocational college students in China. A questionnaire survey was conducted among 1560 students; the University Student Professional Identity Scale, General Self-Efficacy Scale, and Academic Achievement Scale were used as research tools. The responses were recorded using 5-point Likert-type scales. Propose research hypotheses based on structural models. We tested reliability and validity, difference analyses, correlation analyses, regression analyses, and mesomeric effect analysis. There are significant differences in academic achievement among students of different grades, but there is no significant difference in academic achievement among student cadres. The professional identity of vocational college students is significantly and positively predicted academic achievement; self-efficacy partially mediates between professional identity and academic achievement. Professional identity of vocational college students significantly and positively predicted. Academic achievement: self-efficacy partially mediates between professional identity and academic achievement. (1) There is a certain imbalance in the subjects and majors of the study in terms of gender; (2) The exploration of this study is mainly quantitative research, lacking qualitative research; (3) Due to the limitations of research time and method, this study only investigated the real situation for a certain period and lacked the process of long-term follow-up research. University administrators and professional teachers should improve the professional identity of vocational college students to enhance their self-efficacy, promote their academic achievement development, and enhance the vocational, educational, and technical nature of vocational education.